1990
DOI: 10.1172/jci114505
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 stimulates contraction of rat glomerular mesangial cells and potentiates beta-adrenergic-mediated cyclic adenosine monophosphate accumulation.

Abstract: The newly isolated peptide, endothelin-1 (ET-1), is a potent pressor agent that reduces GFR and the glomerular ultrafiltration coefficient. Recent evidence demonstrates that ET-1 mobilizes intracellular Ca2" (ICa2+Ii) in glomerular mesangial cells by activating the phosphoinositide cascade. The present experiments were designed to examine whether ET-1 stimulates mesangial cell contraction and regulates the synthesis of PGE2 and cAMP, which dampen vasoconstrictor-induced mesangial contraction. ET-1 (2 1 nM) red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(59 citation statements)
references
References 41 publications
4
54
0
1
Order By: Relevance
“…This change may be due to ET-1 in the renal cells because ET-1 exists not only in the vascular endothelial cells but also in the mesangial cells or tubular cells (Kosaka et al 1989, Simonson & Dunn 1990, Kohan 1991. Fukui et al (1994) reported that increases in ET-1 mRNA (2, 3 kilobases (kb)) in isolated glomeruli from diabetic rat kidney were partly reversed by enalapril treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This change may be due to ET-1 in the renal cells because ET-1 exists not only in the vascular endothelial cells but also in the mesangial cells or tubular cells (Kosaka et al 1989, Simonson & Dunn 1990, Kohan 1991. Fukui et al (1994) reported that increases in ET-1 mRNA (2, 3 kilobases (kb)) in isolated glomeruli from diabetic rat kidney were partly reversed by enalapril treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen (32), kidney (27), vascular smooth muscle cells (33,23), and adrenal glomerulosa cells (22), and could explain the potent long lasting effect of this peptide (1,6). Elevation of intracellular free Ca2+ and not of cAMP has been invoked to mediate the action of ET-1; only in mesangial cells (34) and Swiss 3T3 fibroblasts (35) has a small increase (34) or decrease (35) in cAMP levels been reported in response to ET-1. Our results clearly show that ET-1 does not affect cAMP levels in rat hepatocytes (Table I), but provokes oscillations in cytosolic free Ca2" in single aequorin-injected hepatocytes, similar to that produced by other Ca2+ mobilizing hormones (1 1, 19).…”
Section: Discussionmentioning
confidence: 99%
“…RMIC were stained using previously described methodology (19). Briefly, cells were incubated in KRB alone or containing 10 nM ET-1 or 10 nM AVP for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%